2001
DOI: 10.1081/pln-100106976
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Thallium by Vegetables: Its Significance for Human Health, Phytoremediation, and Phytomining

Abstract: Eleven common vegetables (green bean, beetroot, green cabbage, lettuce, onion, pea, radish, spinach, tomato, turnip, and watercress) as well as the thallium hyperaccumulator Iberis intermedia, were grown in pot trials containing 0.7 and 3.7 mg/kg thallium added to a silt loam soil. The aims of the experiments were threefold: to estimate risks to human health of vegetables grown in thallium-rich soils, to demonstrate the potential of crops of these plants to remove thallium from polluted soils (phytoremediation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 9 publications
3
35
0
Order By: Relevance
“…The observed BAC value is low compared to values published for other vegetables. LaCoste et al (2001) found BAC-values in 11 plants ranging from 0.76 to 87.0 with the lowest value for tomato and highest values for the cabbage family (Brassicaceae). Uptake of Tl depends on the soil conditions; it will increase with increasing soil acidity and Tl originating from pollution sources has been found more available than Tl with a geogenic origin (Kazantzis 2000).…”
Section: Relations Between Soil Parameters and Water Spinach Element mentioning
confidence: 95%
“…The observed BAC value is low compared to values published for other vegetables. LaCoste et al (2001) found BAC-values in 11 plants ranging from 0.76 to 87.0 with the lowest value for tomato and highest values for the cabbage family (Brassicaceae). Uptake of Tl depends on the soil conditions; it will increase with increasing soil acidity and Tl originating from pollution sources has been found more available than Tl with a geogenic origin (Kazantzis 2000).…”
Section: Relations Between Soil Parameters and Water Spinach Element mentioning
confidence: 95%
“…The normal Tlcontent in these species ranges between 0.01 and 0.1 mg g À1 wet weight. Thallium uptake was also demonstrated by food plants such as beans, silver beet, carrots, lettuce, and spinach from experimental slag-or Tl-sulfate-contaminated soils (Bunzl et al 2001, LaCoste et al 2001. Hyperaccumulation of thallium was found in Iberis intermedia and Biscutella laevigata (both Brassicaceae) (LaCoste et al 2001).…”
Section: Waste Products and Industrial Emissionsmentioning
confidence: 86%
“…For instance, the species Alyssum bertolonii and Berkheya coddii have a high potential for extracting Ni, due to their high biomass and a Ni concentration of 1 % in the dry matter . Other metals such as gold, thallium, and cobalt have been extracted from tailings or other residues of low commercial value (LaCoste et al 2001 ;Keeling et al 2003 ). Heavy metal phytoextraction refers to the use of plants that can remove contaminants from soil and accumulate them in a harvestable part in a process alongside water and nutrient absorption by roots.…”
Section: The Technologymentioning
confidence: 99%